Nurturing creativity : an essential mindset for young children's learning - Isbell, Rebecca T.; Yoshizawa, Sonia Akiko (Washington, DC : National Association for the Education of Young Children, 2016)
Young children have great capacity for creativity that thrives when it is nurtured. Early childhood teachers have the opportunity to inspire children's innovative thinking and doing by: Including creative opportunities across all domains of learning ; Designing a beautiful space that encourages children's experimentation and play ; Extending children's learning and challenging their thinking ; Documenting children's thought processes and displaying their work ; Involving families and the community in children's creative endeavors ; Reflecting on your beliefs and practices about creativity and nurturing your own creativity ; Learn how to support children as they problem-solve, explore and share new ideas, and collaborate with others, and watch their confidence and capableness grow.
What is creative thinking and why do we need it now? -- Understanding the creative process -- The environment: a look inside classrooms that inspire creativity -- Characteristics of creative children and adults -- What is the teacher's role? -- The role of play in creativity -- Extending thinking with materials -- Displaying and documenting children's work -- Expanding the community of support.
Includes bibliographical references.
WorldShare provided record.
Keywords: Creative ability in children -- Study and teaching (Early childhood).; Creative thinking in children -- Study and teaching (Early childhood).; Arts -- Study and teaching (Early childhood).; Creative activities and seat work -- Study and teaching (Early childhood).